Valorization of Cassava Peel and Shrimp Shell Waste for Bioplastic Film Development: Extraction, Characterization, and Response Modeling - Picar, André E; Molina, Bianca Isabel; Dejuras, Joachim Florenzo; Veran, Maria Julliana; Estrellado, John Ray (Future Science / FSH-PH Publications, 2025)
Accumulation of waste food materials, such as cassava and shrimp peels, continues to contribute to rise in greenhouse emissions. This study aims to produce a bioplastic film made from extracted cassava peel starch (CPS) and shrimp shell chitosan (SSCHT), plasticized with sorbitol (SOR) using a constrained D-optimal mixture design. Films were assessed in terms of tensile strength, elongation at break, contact angle, opacity, and functional groups. Significant models were generated in terms of tensile strength (p = 0.0148), contact angle (p = 0.1049) and opacity (p = 0.6529). Cassava peel starch had a significant (p < 0.001) effect on tensile strength due to hydrogen bonding with chitosan, whereas elongation at break was significantly (p = 0.0017) affected by sorbitol due to its structural similarity to starch and larger molecular weight as compared to glycerol. Contact angle increased with the incorporation of shrimp shell chitosan (p = 0.4647) by minimizing hydrophilic regions for external water molecule penetration. Opacity was significantly (p = 0.0013) reduced by the incorporation of cassava peel starch due to the refraction of swollen starch granules. Fourier-Transform Infrared Spectroscopy (FTIR) verified the interactions in the CPS/SSCHT/SOR bioplastic film, while thermogravimetric analysis (TGA) provided insights on thermal stability of the bioplastic for industrial use. This study provides insight into the potential of food waste valorization using green extraction methods in producing environmentally friendly bioplastics for hard packaging applications.